A atenção à saúde da mulher no Estado de São Paulo, Brasil: avaliação de serviços de atenção primaria à saúde - Couto, Caroline Eliane [UNESP]; Nemes, Luceime Olívia [UNESP]; Zarili, Thais Fernanda Tortorelli [UNESP]; Mendonça, Carolina Siqueira [UNESP]; Gomes, Eduardo de Sousa [UNESP]; Pissatto, Stella Bianca Gonçalves Brasil; Nunes, Hélio Rubens de Carvalho [UNESP]; Castanheira, Elen Rose Lodeiro [UNESP] (FapUNIFESP (SciELO), 2025)
This study aimed to assess the organization of women's health care within primary health care services. This evaluative research utilized indicators derived from a survey conducted in the state of São Paulo, Brazil, in 2022 by the QualiAB system. A total of 2,269 services, located in 356 municipalities, were evaluated using an assessment matrix comprising 46 indicators grouped into five domains. Overall performance was estimated based on the average score obtained. Using the K-means clustering technique, the services were grouped into three quality clusters, and associations between these clusters and service characteristics were analyzed using multinomial linear regression. The overall performance of the 2,269 evaluated services was 66.4%. The highest performance was observed in the "postpartum care" domain (81.6%), followed by "reproductive planning" (68.8%), "breast and cervical cancer prevention and screening" (68.6%), "prenatal care" (61.9%), and "care for women in situations of violence" (47.2%). A higher frequency of "traditional" actions related to maternal and child health was observed, along with a lower frequency of health education and promotion activities. The variables "population size (> 200,000 inhabitants)", "recruitment of pregnant women by community agents", "use of epidemiological data", and "frequency of team meetings" were positively associated with higher quality. The identified weaknesses lie within the governance of local teams and municipal management, highlighting the need for professional development and the reorganization of work processes to effectively implement the guidelines for comprehensive women's health care.